Peran Tata Kelola Perusahaan Dalam Kinerja Operasional dan Kinerja Pasar Di Indonesia - Amrie Firmansyah, Novi Damayanti, (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2021)
This study investigates the association's corporate governance and the company's operational performance and market performance. The research data is sourced from financial reports and annual reports of consumer goods sector companies listed on the Indonesia Stock Exchange from 2015 to 2019, obtained from www.idx.co.id. Based on purposive sampling, the total sample in this study amounted to 120 observations. Hypothesis testing in this study uses multiple regression analysis for panel data. This study suggests that corporate governance is negatively associated with a company's operational performance but is not associated with the company's market performance. However, the implementation of governance in Indonesia is still administrative and has not been implemented by companies properly. This research indicates that the Financial Services Authority needs to improve policies and monitor issuers related to governance implementation.